2021
DOI: 10.1016/j.envres.2021.111331
|View full text |Cite
|
Sign up to set email alerts
|

County-level exposures to greenness and associations with COVID-19 incidence and mortality in the United States

Abstract: Background COVID-19 is an infectious disease that has killed more than 555,000 people in the US. During a time of social distancing measures and increasing social isolation, green spaces may be a crucial factor to maintain a physically and socially active lifestyle while not increasing risk of infection. Objectives We evaluated whether greenness was related to COVID-19 incidence and mortality in the US. Methods We downloaded data on COVID-19 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 35 publications
5
50
1
Order By: Relevance
“…Population density Linear mixed effect models After accounting for known mechanisms behind transmission rates, we found that park use decreased residual pre-peak case rates, especially when greenspace was low and contiguous. 11 Klompmaker, Hart [ 40 ] US Cross-sectional County 3089 Incidence NDVI Negative binomial mixed models 1. An increase of 0.1 in NDVI was associated with a 6% decrease in COVID-19 incidence rate.…”
Section: Table A1mentioning
confidence: 99%
“…Population density Linear mixed effect models After accounting for known mechanisms behind transmission rates, we found that park use decreased residual pre-peak case rates, especially when greenspace was low and contiguous. 11 Klompmaker, Hart [ 40 ] US Cross-sectional County 3089 Incidence NDVI Negative binomial mixed models 1. An increase of 0.1 in NDVI was associated with a 6% decrease in COVID-19 incidence rate.…”
Section: Table A1mentioning
confidence: 99%
“…Research has also shown that youth ( Jackson et al, 2021 ) and adults ( Cindrich et al, 2021 ; Poortinga et al, 2021 ; Pouso et al, 2021 ; Ribeiro et al, 2021 ) who maintained outdoor activity during the pandemic reported better psychological health outcomes than those who did not go outside. Greenspace exposure, often measured based on proximity and access, has also been associated with lower COVID-19 mortality, infection, and racial disparities in infection rates in the United States ( Klompmaker et al, 2021 ; Lu et al, 2021a , 2021b ; Pan et al, 2021 ; Russette et al, 2021 ; You and Pan, 2020 ); in other parts of the world, however, associations between COVID-19 mortality and infection rates and greenspace are mixed ( Labib et al, 2021 ; Ribeiro et al, 2021 ; Viezzer and Biondi, 2021 ; You et al, 2020 ). Collectively, these studies highlight the wide range of health benefits that outdoor recreation and park use might provide in the era of COVID-19 ( Soga et al, 2021a ), yet underscore the need for additional research.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al (2020) studied 30,556 zip code level COVID-19 cases during June 2020 and observed that zip codes with higher levels of greenery along streets (>30%) had fewer COVID cases than zip codes with lower levels of greenery along streets. Klompmaker et al (2021) found that higher neighborhood greenness was significantly associated with lower COVID incidence rates among 3,089 U.S. counties (6% reduction per 0.1 increase in NDVI), but greenness was not related to COVID mortality at population level but correlated for subgroup level mortality. Several other studies investigated COVID outcomes with residential greenness in counties across the USA and found higher residential greenness associated with reduced COVID-19 mortality (Lee et al, 2021;Lu et al, 2021a;Russette et al, 2021).…”
Section: Covid-19 Incidence and Mortalitymentioning
confidence: 92%
“…In the U.S., white respondents reported lower levels of psychological wellbeing when they felt that the COVID-19 pandemic had restricted their access to nature; in contrast, nonwhite respondents reported higher levels of psychological well-being when they felt restrictions in nature access during the pandemic (Tomasso et al, 2021). U.S. counties with greater shares of Black residents showed no differences in associations between green space and COVID incidence than counties with lower shares of Black residents; further, counties with the smallest shares of Black residents showed positive associations between green space and COVID-related mortality (Klompmaker et al, 2021). This finding suggests harmful associations between green space and COVID mortality in areas with low levels of Black residents.…”
Section: Variations In Nature Contact Changes and Nature-health Associations By Sociodemographic Economic And Racial/ethnic Groupsmentioning
confidence: 92%
See 1 more Smart Citation